Studies on PVA/MAA:EA polymer blend films modified by Fe3+ doping - Neeruganti Obularajugari Gopal; Mahammad Hussain Basha; Ojha Pravakar; Yedurupaka Madhav Kumar (Applied Microscopy)
Abstract Pristine and Fe (1.0, 2.0, 3.0, 4.0 and 5.0 mol%) doped Polyvinyl alcohol/Methacrylic Acid- Ethyl Acrylate (PVA/MAA:EA) polymer blend films were prepared by solution casting method and characterized by various techniques. TGA analysis validates the occurrence of three distinct weight loss steps attributed to removal of volatile substances from both the surface and interior of the material, as well as the decomposition of the polymer. X-ray diffraction (XRD) investigations confirm a decrease in crystallinity as the dopant concentration increases. Scanning electron microscope (SEM) micrographs show uniform morphology. Fourier transform infrared (FTIR) spectrum exhibits bands characteristic of stretching and bending vibrations of O–H, C–H, C = C and C–O groups and the changes in the spectrum with dopant concentration show the miscibility of dopant with the polymer blend. UV–visible absorption spectra demonstrate the decrease of optical band gap as the concentration of Fe rises and exhibit absorption bands corresponding to the transitions 6A1g → 4A1g and 6A1g → 4T2g of Fe3+ ions in distorted octahedral symmetry. Electron paramagnetic resonance (EPR) spectra exhibit resonance signals one around g = 2.12 attributed to Fe3+ ions in the distorted octahedral environment and the other signal around g = 6.8 due to Fe3+ ions in rhombic symmetry. The number of spins engaged in the resonance as a function of dopant concentration is determined through EPR analysis and the paramagnetic susceptibility is estimated. The conductivity of Fe3+ ions doped PVA/MAA:EA polymer blend films increases with an increase in Fe3+ concentration, which is explained in terms of an increase in the amorphous phase due to doping.